Ultrasonic Study of Dipole-Dipole Interactions in Ternary Liquid Mixtures at Different Temperatures - THIRUMARAN, S.; ANBUSELVI, P. (Asian Journal of Chemistry, 2010)
The ultrasonic velocity, density and viscosity have been measured for the mixtures of primary alkanols, namely, 1-propanol, 1-butanol and 1-pentanol with aniline in toluene at 303, 308 and 313 K. The experimental data have been used to calculate the acoustical parameters namely adiabatic compressibility (β), free length (Lf), free volume (Vf), internal pressure (πi), acoustic impedance (Z) and molar volume (Vm). The excess values of some of the above parameters are also evaluated and discussed in the light of molecular interaction present in the mixtures. It is observed that the alkanols form strong dipole-dipole interactions with aniline. However, no complex formation or charge-transfer reactions were observed in the present study. The elevation of temperature in the present study, which may probably, would be caused from the fact that thermal energy facilitates an increase in the molecular separation in the liquid mixtures.